Avaliação imunohistoquímica da expressão de receptores de estrogênio (RE) e de progesterona (RP), em neoplasias escamosas intraepiteliais e invasoras do colo uterino : correlações com a progessão tumoral - Silva, Francisco José Bastista da (2004)
Cervical cancer is associated with a very high incidence (16.3/100.000) and mortality (1,627/100.000) in northeastern Brazil; strongly correlated with HPV (98% by PCR). However, the relation between the stages of cervical cancer and the hormonal receptors ER and PR remains unclear. This study presents an immunohistochemical analysis of the morphological expression of the hormonal receptors ER and PR in different stages of cervical cancer. One hundred forty-four samples were obtained for analysis from the cervices of patients at a cancer screening service in northeastern Brazil in the years 2001 and 2002. Following gynecological examination colposcopically guided biopsies revealed apparently abnormal epithelia. Subsequently the specimens were classified in scores (1 to 9) according to hormonal receptor expression: intensity reaction (1 to 3) versus cell-marked dispersion (1 to 3).Sixty-two cases of LSIL, 41 cases of HSIL and 41 cases of ISCC were compared with regard to menstrual cycle and age. In SIL nuclear reactivity to ER decreased gradually from the lower to the higher stages, including that of ISCC. Stromal marked nuclei were seen in SIL and tended to increase in ISCC in spite of displaying lower scores. There were no significant differences for ER and PR expression related to menstrual cycle phases or menopausal status. Pre- and post-menopausal analyses showed no significant variation in the expression of either ER or PR.